Processing Stability and the Significance of Variation in Extrusion Speeds and Temperatures on SSB® 55 Pharma Grade Shellac for Oral Drug Delivery - Gately, Noel; Kennedy, James (Journal of Manufacturing and Materials Processing, 2017)
The melt-extrusion process is utilized in the pharmaceutical arena for the manufacturing of a variety of dosage forms and formulations, including solid dispersions. This technology is considered an efficient and continuous dosage form manufacturing method. However, there are potential challenges mainly because, during hot-melt extrusion, polymers are subject to mechanical and thermal degradation. Mechanical degradation may be induced by the shear effects imposed by the rotating screw. Thermal degradation results from high temperatures and includes random scission, scission from the ends of the polymer and unzipping of substitute groups. This paper endeavors to understand the impact of thermal and/or mechanical components of the melt-extrusion process on the stability of a pH sensitive polymer, namely Shellac. Correlation between the screw speeds and processing temperature profile was examined in the context of the overall degradation profile of the polymer. The results suggest that the processing stability of Shellac was reliant on optimization of screw speed (rpm) and process temperature.